2022
DOI: 10.3390/ijms231810916
|View full text |Cite
|
Sign up to set email alerts
|

A Novel L-Phenylalanine Dipeptide Inhibits the Growth and Metastasis of Prostate Cancer Cells via Targeting DUSP1 and TNFSF9

Abstract: Prostate cancer (PCa) is a common malignant cancer of the urinary system. Drug therapy, chemotherapy, and radical prostatectomy are the primary treatment methods, but drug resistance and postoperative recurrence often occur. Therefore, seeking novel anti-tumor compounds with high efficiency and low toxicity from natural products can produce a new tumor treatment method. Matijin-Su [N-(N-benzoyl-L-phenylalanyl)-O-acetyl-L-phenylalanol, MTS] is a phenylalanine dipeptide monomer compound that is isolated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It has been shown that TNFSF9 can promote metastasis of pancreatic cancer through Wnt/Snail signaling and macrophage M2 polarization 30 . It has also been shown that by targeting TNFSF9 can inhibit the growth and metastasis of prostate cells 31 . However, unfortunately, there are no relevant experiments in cervical cancer that can draw similar conclusions as the previous ones.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that TNFSF9 can promote metastasis of pancreatic cancer through Wnt/Snail signaling and macrophage M2 polarization 30 . It has also been shown that by targeting TNFSF9 can inhibit the growth and metastasis of prostate cells 31 . However, unfortunately, there are no relevant experiments in cervical cancer that can draw similar conclusions as the previous ones.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the influence on immune signaling, our in vitro and sequencing experiments revealed that ZNF643 is involved in cell migration, invasion, and adhesion. While TNFSF9 was previously demonstrated to play a role in these processes [34,35], SYNE3, another gene regulated by ZNF643, is implicated in migratory activities [36,37]. SYNE3 is a part of the linker of the nucleoskeleton and cytoskeleton (LINC) complex, which is crucial for the organization and dynamics of the perinuclear cytoskeleton [37,38].…”
Section: Discussionmentioning
confidence: 99%